An allometric model to estimate total leaf area of banana plants of the cultivar Vitória (AAAB) - Padovan,Maria da Penha (2022)
ABSTRACT: The plants physiological processes such as transpiration and photosynthetic efficiency are directly related to leaf area, which is difficult to quantify in a nondestructive manner. To generate a model to estimate the total leaf area of plants of banana cv. Vitória, simple and multiple linear regressions utilizing the length and width of the third leaf, the product of length and width of the third leaf, and the total number of leaves of ‘Vitória’ plants, were tested. The data to develop the model were obtained from ‘Vitória’ banana plants from different edafoclimatic conditions and management. The best performance of the model was obtained using stepwise multiple regression with r2=0.93 and r2= 0.94. Validation of the model resulted in an r2 of 0.74.